"Estudio comparativo entre SQL y NOSQL basado en el rendimiento, seguridad, e integridad de los datos" - Moreira Resabala, Wilmer Joel (2016)
Through this research project entitled “Comparative study between SQL and NOSQL BASED ON PERFORMANCE, SECURITY, AND INTEGRITY OF DATA”, fundamentals engine databases, both relational (SQL) and non-relational (NoSQL) are exposed depending on their indicators, previously set for later verification. The research is done in order to increase the level of knowledge about SQL and NoSQL data in our midst, the same that will determine the database manager viable data according to the indicators proposed, because these methods are they complement, ie, must choose non-relational relational DBMS or under the circumstances necessary for use. In addition, it determines how response times are obtained when using large volumes of information using a database manager to store, using indicators based on performance, integrity and security of data. In the end it is shown that serves as a support tool, because it allows choose a manager database either relational or type non-relational, thanks to the advantages and disadvantages encountered when working with BD on aspects of the indicators above.